Perceived parenting styles differ between genders but not between elite athletes and controls - Serge Brand; Markus Gerber; Johannes Beck; et al (Dove Medical Press, 2011)
Serge Brand1, Markus Gerber2, Johannes Beck1, Nadeem Kalak1, Martin Hatzinger1,3, Uwe Pühse2, Edith Holsboer-Trachsler11Depression and Sleep Research Unit, Psychiatric Hospital of the University of Basel, Basel, Switzerland; 2Institute of Exercise and Health Sciences, University of Basel, Basel, Switzerland; 3Psychiatric Hospital, Solothurn, SwitzerlandAbstract: For adolescent elite athletes, parental financial and emotional support is crucial. However, parents of elite athletes may be critical and demanding. Moreover, there is evidence that girls report more favorable perceived parenting styles compared with boys. The aim of the present study was to investigate perceived parenting styles among female and male adolescent elite athletes and controls. We sampled 258 adolescent elite athletes (139 females, 119 males) and 176 controls (139 females, 37 males). Participants completed a questionnaire to assess perceived parenting styles (support, commendation, reproach, restriction, inconsistency). Results showed that parenting styles did not differ between athletes and controls, except for restriction, for which athletes reported lower levels. Female adolescents had higher scores for positive and lower scores for negative perceived parenting styles.Keywords: parenting style, gender, elite athletes, controls